Effectiveness of Using the PBL Models in Physical Education Based on Active Learning Time - Prawesti, Putri; Rusdiyanto, Rajip Mustafillah; Sofyan, Davi; Yudha, Brio Alfatihah Rama; Nurhayati, Maya; Rudi, Rudi (Universitas Majalengka, 2024)
This study aims to determine the effectiveness of using the PBL learning model in physical education based on students' active learning hours. This research is a type of qualitative descriptive research. The population in this study were high school students with samples of science classes and social studies classes. The study results concluded that the level of time effectiveness obtained by physical education teachers using the PBL model on students' active learning time was in the low category. Overall, the results of this study need to be carried out further so that the results can be generalized.